Remote Sensing Image-Based Comprehensive Monitoring Detection Platform for Coastal Tidal Mudflat Ecological Development - Xiao, Shengjun; Yi, Lin; Wang, Zengjie; Liu, Huiyu; Gao, Hong; Yu, Zhaoyuan (Frontiers in Environmental Science, 2022)
Considering the embarrassments related to inadequate safety monitoring detection and chaotic development order during the current ecological development of coastal tidal mudflat, we put forward a remote sensing image-based comprehensive monitoring detection platform integrating image data acquisition, mechanism analysis, comprehensive evaluation and intelligent monitoring detection for coastal tidal mudflat ecological development. The platform includes imaging and data fusion technology, comprehensive evaluation and spatial layout optimization technology and dynamic safety monitoring and early warning technology. A case study in Dafeng coastal tidal mudflat was conducted. The results show that our research can provide substantial reference for the coordination, dynamic management and comprehensive regulation for the ecological development of coastal tidal mudflat.